THE RISK FACTORS FOR WASTING IN CHILDREN AGED 24–59 MONTHS IN RURAL AREAS OF WEST SUMATRA PROVINCE: ANALYSIS OF SKI 2023 DATA : WASTING IN CHILDREN AGED 24–59 MONTHS - Ul-Humami, Auliya; Nursal, Dien Gusta Anggraini; Widoyo, Ratno (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2025)
Background: Wasting is still a major health problem in toddlers, especially in rural areas. This study aims to analyze the risk factors of wasting in children under five years of age 24-59 months in rural areas of West Sumatra Province. Methods: This study used a quantitative approach with a cross-sectional design. The study used secondary data from the Indonesian Health Survey in 2023 with a sample size of 541 toddlers. Data analysis was conducted bivariate using the chi-square test. Results: The results of the analysis showed that of the five variables studied, the history of infectious diseases (p=0.001) and vitamin A supplementation (p=0.003) had a significant association with the incidence of wasting in children aged 24-59 months in rural areas of West Sumatra Province. Meanwhile, economic status (p=0.414), environmental sanitation (p=0.104), and drinking water source (p=0.094) had no significant association. Conclusion: In rural areas, infectious diseases and lack of vitamin A supplementation were the causes of wasting. Health promotion and prevention of infectious diseases need to be evaluated and improved including efforts to increase the immune system of children under five.